Pemberdayaan Penyandang Disabilitas Melalui Pelatihan Berbahasa Inggris untuk Spa Therapist dan Pemasaran Digital di Sentra Mahatmiya Tabanan: Empowerment of Persons with Disabilities Through English Language Training for Spa Therapists and Digital Marketing at the Mahatmiya Center Tabanan - Kadek Feni Aryati; Putu Sri Darmayanti; I Putu David Adi Saputra (Journal of Community Development and Disaster Management, 2025)
This community service program aims to empower people with disabilities at Sentra Mahatmiya Tabanan, Bali, through intensive English language and digital marketing training. Sentra Mahatmiya is a social enterprise employing people with disabilities, but it faces challenges such as limited English proficiency and a lack of digital marketing skills. To address these issues, the program includes two main components: applied English training for spa therapists and comprehensive digital marketing training. The English training focuses on spa-related vocabulary, customer service communication, and practical simulations, while the digital marketing component covers content creation, website management, online advertising, and basic SEO strategies. The results show improved English and digital skills among participants, leading to increased income and economic independence. Evaluation was conducted through observations, written tests, and interviews. This program is expected to serve as a model for empowering people with disabilities in the tourism sector and small businesses.